2019
DOI: 10.1177/0165551519837182
|View full text |Cite
|
Sign up to set email alerts
|

Understanding data search as a socio-technical practice

Abstract: Open research data are heralded as having the potential to increase effectiveness, productivity, and reproducibility in science, but little is known about the actual practices involved in data search. The socio-technical problem of locating data for reuse is often reduced to the technological dimension of designing data search systems. We combine a bibliometric study of the current academic discourse around data search with interviews with data seekers. In this article, we explore how adopting a contextual, so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 42 publications
(191 reference statements)
1
58
0
1
Order By: Relevance
“…Given how colleagues figure prominently as sources of information for web-based species occurrence information systems, the human dimensions and social networks (not just electronic but human networks in general) of professionals should figure more prominently in outreach and communication strategies aimed at improving discoverability of web-based species occurrence information systems. A review of data retrieval practices across scientific disciplines found that data retrieval is a process that involves not only the user and the information system, but rather includes the user's social networks and personal exchanges as the user navigates finding, obtaining and evaluating data for his or her use [45]. Our results support this broader view of data retrieval as a process that involves social aspects when using data from web-based species occurrence information systems.…”
Section: Plos Onesupporting
confidence: 70%
See 1 more Smart Citation
“…Given how colleagues figure prominently as sources of information for web-based species occurrence information systems, the human dimensions and social networks (not just electronic but human networks in general) of professionals should figure more prominently in outreach and communication strategies aimed at improving discoverability of web-based species occurrence information systems. A review of data retrieval practices across scientific disciplines found that data retrieval is a process that involves not only the user and the information system, but rather includes the user's social networks and personal exchanges as the user navigates finding, obtaining and evaluating data for his or her use [45]. Our results support this broader view of data retrieval as a process that involves social aspects when using data from web-based species occurrence information systems.…”
Section: Plos Onesupporting
confidence: 70%
“…Our definition of web included not only web-based species occurrence information systems but also search engines and other websites. The use of search engines [28,45,109] and other…”
Section: Sources Of Data and Informationmentioning
confidence: 99%
“…For selected disciplines, similarities in how users search for research data are identified. In [11], the same group of authors investigate the search for research data from a socio-technical perspective by combining results from the literature with conducted interviews.…”
Section: Plos Onementioning
confidence: 99%
“…The data scientists need understand the domain context. They not only have to negotiate the access to data [44] but also negotiate the definition and scope of their tasks. On the other hand, the engineers need to instruct the data scientists and interpret their results.…”
Section: Skills Of a Data Scientist -The Myth Of The Data Science Unimentioning
confidence: 99%